Polymorphic variation in TPMT is the principal determinant of TPMT phenotype: A meta‐analysis of three genome‐wide association studies. Issue 5 (1st February 2017) - Tamm, R; Mägi, R; Tremmel, R; Winter, S; Mihailov, E; Smid, A; Möricke, A; Klein, K; Schrappe, M; Stanulla, M; Houlston, R; Weinshilboum, R; et al.
Abstract : Thiopurine‐related hematotoxicity in pediatric acute lymphoblastic leukemia (ALL) and inflammatory bowel diseases has been linked to genetically defined variability in thiopurine S‐methyltransferase (TPMT) activity. While gene testing of TPMT is being clinically implemented, it is unclear if additional genetic variation influences TPMT activity with consequences for thiopurine‐related toxicity. To examine this possibility, we performed a genome‐wide association study (GWAS) of red blood cell TPMT activity in 844 Estonian individuals and 245 pediatric ALL cases. Additionally, we correlated genome‐wide genotypes to human hepatic TPMT activity in 123 samples. Only genetic variants mapping to chromosome 6, including the TPMT gene region, were significantly associated with TPMT activity ( P < 5.0 × 10 ‐8 ) in each of the three GWAS and a joint meta‐analysis of 1, 212 cases (top hit P = 1.2 × 10 ‐72 ). This finding is consistent with TPMT genotype being the primary determinant of TPMT activity, reinforcing the rationale for genetic testing of TPMT alleles in routine clinical practice to individualize mercaptopurine dosage.